1997
DOI: 10.3109/00048679709073822
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Childhood Sexual Abuse in Adult Female Psychiatric Patients

Abstract: The long-term effect of childhood sexual abuse is increased incidence of deliberate self-harm and is unrelated to any specific diagnosis. Despite more severe initial impairment, psychotherapy was effective for patients with a history of childhood sexual abuse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 11 publications
0
9
0
1
Order By: Relevance
“…Other factors might account for the relationship, such as other adverse events or circumstances in childhood, and subsequent re‐victimization. However, other mental health problems are related to child abuse after controlling for these potentially mediating variables (6, 9, 131). After controlling for other childhood disadvantages, women whose CSA involved intercourse were 12 times more likely than non‐abused females to have had psychiatric admissions, and 26 times more likely to have tried to kill themselves (3).…”
Section: Resultsmentioning
confidence: 99%
“…Other factors might account for the relationship, such as other adverse events or circumstances in childhood, and subsequent re‐victimization. However, other mental health problems are related to child abuse after controlling for these potentially mediating variables (6, 9, 131). After controlling for other childhood disadvantages, women whose CSA involved intercourse were 12 times more likely than non‐abused females to have had psychiatric admissions, and 26 times more likely to have tried to kill themselves (3).…”
Section: Resultsmentioning
confidence: 99%
“…The relationship between child abuse and mental health problems in adulthood remains after controlling for potentially mediating variables such as socioeconomic status, marital violence, parental substance abuse and psychiatric history, and other childhood traumas (Kendler et al 2000; Pettigrew & Burcham 1997). After controlling for factors related to disruption and disadvantage in childhood, a community survey found that New Zealand women whose CSA involved intercourse were 12 times more likely than non‐abused females to have had psychiatric admissions (Mullen et al 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Although the primary and unique role of child abuse in the development of deliberate self-harm (DSH) is debated (Klonsky and Moyer, 2008), child abuse may affect the range and severity of psychiatric symptoms and psychological problems among persons with DSH (Forman et al, 2004). Despite the strong impact of childhood abuse among DSH patients, only a few uncontrolled studies have examined whether the presence of a history of abuse limits an individual's response to treatment (Arnold et al, 2003;Pettigrew and Burcham, 1997;Söderberg et al, 2004) with mixed results. However, the relationship between a history of abuse and treatment outcome for DSH has never been studied in a randomized controlled clinical trial.…”
mentioning
confidence: 99%